Infrastructure - Bokov, Andrey (project baikal, 2021)
The history of cultural space is viewed as a history of constant and necessary modernization of infrastructure. The main feature of infrastructure is the network organization and the constructive role of hub-nodes and connections and their bent for rationalization and transnational trends. The power, directions and goals of infrastructure determine the development of cities. Modern strategies for general social development imply the emergence of efficient communication corridors, highway networks and hubs located along the perimeter of the country, determining the country’s gravitation toward global connections and interactions. The development of quality infrastructure is a contribution to the future and an area of the authorities’ responsibility.
Keywords: city; network organization; infrastructure; global trends; urban planning; modernization